PENGARUH PENGGUNAAN MEDIA â€œSEGARâ€ DAN PERMAINAN â€œBASISâ€ PADA PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Fauziyah, Priliyani; Maulana, M.; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
This research is based on the idea that the "Segar" media-assisted contextual approach and "Basis" games can improve the students'comprehension skill of mathematical. This research uses a quasi-model design of non-equivalent control group experiments. The samples were chosen based on the basic comprehension skill of mathematical test scores that have comparable capability, so that the samples taken are in one of primary schools in Sub-district of Pleres SDN 1 Tegalsari, class IVA as experimental class 1 and IVB as experimental class 2. Instruments used in this researcharecomprehension skill of mathematical test, student activity observation format, teacher performance observation format, and questionnaire. Data acquisition in this research was analyzed through SPSS 16.0 for windows program. From the analysis that has been done, then obtained the calculation results of 46.10% variation of achievement comprehension skill ofmathematical at the end of learning contextual approach with media aid "Segar". While the contextual approach of game "Basis" offers a variation of achievement of comprehension skill improvement of 66.75%.